2015
DOI: 10.1051/kmae/2014038
|View full text |Cite
|
Sign up to set email alerts
|

The disturbance-driven changes of periphytic algal communities in a Danubian floodplain lake

Abstract: Key-words:periphyton, algae, artificial substrata, disturbance, floodplain Disturbance event-driven changes in periphytic algal communities were studied in a Danubian floodplain using artificial substrata (glass slides). The hydrological regime of the river-floodplain system strongly influenced the physical and chemical environment of the investigated lake. Directional changes in the algal communities, demonstrated by the results of non-metric multidimensional scaling, indicated three distinct phases in periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Benthic algae or phytobenthos are rarely in the focus of interest, although it is investigated in the Pannonian ecoregion, more specifically in the Danubian floodplain (Žuna Pfeiffer et al, 2015). Benthic algae have also been investigated in experiments on tufa barriers and artificial substrates in karstic lakes (Kralj et al, 2006;Plenković-Moraj et al, 2002), but never in small mountainous rivers.…”
Section: Discussionmentioning
confidence: 99%
“…Benthic algae or phytobenthos are rarely in the focus of interest, although it is investigated in the Pannonian ecoregion, more specifically in the Danubian floodplain (Žuna Pfeiffer et al, 2015). Benthic algae have also been investigated in experiments on tufa barriers and artificial substrates in karstic lakes (Kralj et al, 2006;Plenković-Moraj et al, 2002), but never in small mountainous rivers.…”
Section: Discussionmentioning
confidence: 99%
“…Rodríguez et al (2011) showed that in humic shallow lakes in Argentina, the structure of the epiphytion assemblages on the emergent rush Schoenoplectus californicus changed in relation to WLFs, showing a major proportion of planktonic, metaphytic, and ticoplanktonic components during high water phases. Diatoms may be good indicators of some disturbance processes, including WLFs (Barbour et al, 1999;Pfeiffer et al, 2015). For example, the small pennate A. minutissimum is often the first species colonizing the substratum, and its relative abundance, lower than 25% of the total diatom abundance, is characteristic for undisturbed water bodies (Barbour et al, 1999).…”
Section: Parametersmentioning
confidence: 99%
“…In general, the reports on the role of zooplankton and fish in shaping epiphyton communities are scarce and mostly experimental (Tall et al, 2006;Abe et al, 2007;Blanco et al, 2008;Guariento et al, 2010). Some anthropogenic disturbances, like man-made water level fluctuations (WLFs), eutrophication or water pollution are also important factors that influence epiphyton (Barbour et al, 1999;Kernan et al, 2010;Pfeiffer et al, 2015). Hydromorphological modifications of lakes, which allow manipulation of water level, may strongly affect epiphyton on emergent macrophytes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also shown that habitat heterogeneity and regional microalgae species richness have a strong influence on richness of periphyton algae communities [ 9 11 ]. Finally, hydrological factors may be as important as nutrient levels in determining periphyton growth [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%